2022
DOI: 10.1097/sga.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Fecal Microbiota Transplantation in Irritable Bowel Syndrome Patients

Abstract: Irritable bowel syndrome (IBS) is a chronic gastrointestinal disease characterized by abdominal discomfort and bloating, diarrhea, and/or constipation. Fecal microbiota transplantation (FMT) is transferring the fecal bacteria and other microorganisms from a healthy person to another. We performed this systematic review and meta-analysis to assess the efficacy of FMT in treating IBS patients. We searched Scopus, PubMed, Cochrane, and Web of Science databases through June 2021 using relevant key words. We includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…The response rate was 33.7% for nonoral placebo vs. 67.8% for capsule treatment (Xu et al, 2019). FMT vs. control was associated with a significantly higher IBS Quality of Life score at 4, 8, 12, and 24 weeks but no difference in IBS Severity Scoring System score (Myneedu et al, 2019;Elhusein and Fadlalmola, 2022).…”
Section: Irritable Bowel Syndromementioning
confidence: 90%
See 2 more Smart Citations
“…The response rate was 33.7% for nonoral placebo vs. 67.8% for capsule treatment (Xu et al, 2019). FMT vs. control was associated with a significantly higher IBS Quality of Life score at 4, 8, 12, and 24 weeks but no difference in IBS Severity Scoring System score (Myneedu et al, 2019;Elhusein and Fadlalmola, 2022).…”
Section: Irritable Bowel Syndromementioning
confidence: 90%
“…Fresh or frozen donor stool administered via colonoscopy or nasojejunal tube all achieved significant improvements (Ianiro et al, 2019;Xu et al, 2019). However, FMT vs. placebo did not significantly improve IBS symptoms at 12 weeks (RR, 1.19; 95% CI, 0.67-2.13; low; Figure 8; Xu et al, 2019;Elhusein and Fadlalmola, 2022). Furthermore, single FMT via colonoscopy or nasojejunal tube vs. autologous FMT or placebo was associated with improvement (RR, 1.59; 95% CI, 1.06-2.39; low), whereas FMT with multiple-dose capsules vs. capsule excipients as placebo was associated with a lower likelihood of global improvement (RR, 0.54; 95% CI, 0.34-0.85; low; Figure 8; Xu et al, 2019).…”
Section: Irritable Bowel Syndromementioning
confidence: 98%
See 1 more Smart Citation
“…However, it remains unclear whether FMT efficacy extends to other gastrointestinal disorders such as IBS. To our best knowledge, eight systematic reviews with meta-analysis have been conducted for evaluating the efficacy of FMT on IBS treatment up-to-now [16][17][18][19][20][21][22][23], four of them in 2022. This number shows the clinical relevance of IBS as well as FMT as therapy.…”
Section: Introductionmentioning
confidence: 99%
“…So far, some meta-analyses have evaluated the efficacy of FMT in the treatment of IBS, and they unanimously concluded that FMT is ineffective for IBS ( 17 19 ). Unfortunately, some recently published RCTs ( 20 22 ) were not included in these analyses, so the conclusions may not represent the real results very well.…”
Section: Introductionmentioning
confidence: 99%